2009
DOI: 10.1051/0004-6361/200811540
|View full text |Cite
|
Sign up to set email alerts
|

The stellar population and complex structure of the bright-rimmed cloud IC 1396N

Abstract: Context. IC 1396N is a bright-rimmed cloud associated with an intermediate-mass star-forming region, where a number of HerbigHaro objects, H 2 jet-like features, CO molecular outflows, and millimeter compact sources have been observed. Aims. We study the complex structure of the IC 1396N core and the molecular outflows detected in the region in detail and reveal the presence of additional YSOs inside this globule. Methods. We carried out a deep survey of the IC 1396N region in the J, H, K broadband filters and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(105 citation statements)
references
References 25 publications
9
96
0
Order By: Relevance
“…There are class III and class II stars around the rim and class I/0 stars inside. Beltrán et al (2009) did a JHK survey of the same bright rim and found few NIR-excess sources and no signs of clustering toward the southern part of the rim. They also found no color or age gradient in the north-south direction.…”
Section: /5mentioning
confidence: 94%
“…There are class III and class II stars around the rim and class I/0 stars inside. Beltrán et al (2009) did a JHK survey of the same bright rim and found few NIR-excess sources and no signs of clustering toward the southern part of the rim. They also found no color or age gradient in the north-south direction.…”
Section: /5mentioning
confidence: 94%
“…Classified as a class 0/I borderline source, this young protostar is associated with a very energetic bipolar outflow. In addition, near-infrared images by Nisini et al (2001) and Beltrán et al (2009) identified a collimated 2.12 μm H 2 jet. The outflows and envelope of this protostar were firstly mapped by Codella et al (2001) and Beltrán et al (2002Beltrán et al ( , 2004b using BIMA and OVRO.…”
Section: Introductionmentioning
confidence: 99%
“…Deep sub-arcsecond 2.12 μm H 2 1-0 S(1) line emission observations carried out with the TNG telescope (Beltrán et al 2009) resolved the emission features spread throughout the region into several chains of knots. In a few cases, these strands of H 2 knots have a jet-like morphology, which suggests that they could trace different flows Beltrán et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a few cases, these strands of H 2 knots have a jet-like morphology, which suggests that they could trace different flows Beltrán et al 2009). Towards the northern part of the globule, Nisini et al (2001) proposed that some of these knots could be associated with the CO molecular outflow discovered by Codella et al (2001), and Beltrán et al (2009) suggested that strand of knots located at both sides of the IR-dark "tail" could be associated with each other and be part of long flows with lengths ranging Based on observations carried out with the IRAM Plateau de Bure. IRAM is supported by INSU/CNRS (France), MPG (Germany), and IGN (Spain).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation